Hemorrhage from cerebral cavernous malformations: The role of associated developmental venous anomalies. (7th July 2020) - Chen, Bixia; Herten, Annika; Saban, Dino; Rauscher, Steffen; Radbruch, Alexander; Schmidt, Boerge; Zhu, Yuan; Jabbarli, Ramazan; Wrede, Karsten H.; Kleinschnitz, Christoph; Sure, Ulrich; Dammann, Philipp
Abstract : Objective: To determine the role of associated developmental venous anomalies (DVAs) in intracranial hemorrhage (ICH) caused by cerebral cavernous malformations (CCMs). Methods: We analyzed patient registry data of 1, 219 patients with cavernous malformations treated in our institution between 2003 and 2018. Patients with spinal and familial CCM and patients without complete MRI data were excluded. The impact of various variables on ICH as a mode of presentation was assessed with multivariate binary logistic regression analysis. Kaplan Meier/Cox regression analysis was performed to analyze cumulative 5-year-risk for (re)hemorrhage and to identify baseline predictors of this outcome. Results: Seven hundred thirty-one patients with CCM were included. Multivariate logistic regression confirmed a statistically significant negative correlation with DVA (odds ratio [OR] 0.635 [95% confidence interval (CI) 0.459–0.878]) and positive correlation with brainstem localization (OR 6.277 [95% CI 4.287–9.191]) with ICH as the mode of presentation. Among 731 patients, 76 experienced (re)hemorrhage during 2, 338 person-years of follow-up. Overall cumulative 5-year risk was 24.1% (95% CI 21.1%–27.5%). Cox regression analysis revealed initial presentation with ICH (hazard ratio [HR] 8.0 [95% CI 3.549–18.122]) and brainstem localization (HR 2.9 [95% CI 1.756–4.765]) as independent baseline predictors of (re)hemorrhage. Presence of DVA added no independent prognostic information (HR 1.1 [95% CI 0.717–1.885]). Conclusion: Patients with CCM with associated DVA are at lower risk to present with ICH. During untreated 5-year follow-up, they showed equal (re)hemorrhage risk compared to patients with CCM without DVA.